2015
DOI: 10.1155/2015/178526
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolic Phenotypes (Metabolically Healthy and Unhealthy Variants) Are Significantly Associated with Prevalence of Elevated C-Reactive Protein and Hepatic Steatosis in a Large Healthy Brazilian Population

Abstract: Background. Among the obese, the so-called metabolically healthy obese (MHO) phenotype is thought to confer a lower CVD risk as compared to obesity with typical associated metabolic changes. The present study aims to determine the relationship of different subtypes of obesity with inflammatory-cardiometabolic abnormalities. Methods. We evaluated 5,519 healthy, Brazilian subjects (43 ± 10 years, 78% males), free of known cardiovascular disease. Those with <2 metabolic risk factors (MRF) were considered metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 24 publications
5
34
1
2
Order By: Relevance
“…On the other hand, when we compared MHNO and MHO they showed differences in BMI, waist circumference and blood pressure, but not in the other components of MetS. We could see that MHO had similar CRP than MSO, as recently found in Brazilian population [29]. Also, when we evaluated the insulin resistance, we found that MHO had significantly lower HOMA index compared to MSO patients, and that MHO and MHNO did not differ with respect to insulin sensibility.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, when we compared MHNO and MHO they showed differences in BMI, waist circumference and blood pressure, but not in the other components of MetS. We could see that MHO had similar CRP than MSO, as recently found in Brazilian population [29]. Also, when we evaluated the insulin resistance, we found that MHO had significantly lower HOMA index compared to MSO patients, and that MHO and MHNO did not differ with respect to insulin sensibility.…”
Section: Discussionsupporting
confidence: 69%
“…After development of hepatic steatosis (HS), MHO+ hepatic steatosis was associated with increased odds of incident diabetes. Similarly, Shaharyar et al [26] documented an increased prevalence and odds of hepatic steatosis in the MHO group as compared to the MHNW group (40% vs 8%, p<0.001 and OR: 5.80; 95% CI 4.72-7.13, respectively).…”
Section: Mho and Subclinical Atherosclerotic Diseasementioning
confidence: 74%
“…This 10 year 'lag' period may explain the findings in initial published reports, which labeled MHO as a benign phenotype; since the risk increase is only evident after 10 years, studies with shorter follow-up durations would have yielded negative results despite the existence of a true association. Some studies suggest that metabolically healthy individuals may be younger than their metabolically unhealthy counter parts suggesting that over time, they too will develop CVD [25,26]. Additionally, the conversion of MHO to the higher risk MUO over time may explain this effect, as in 2 studies, MHO was seen to convert to MUO in 34.2% [27] and >50% of subjects over prolonged follow-up [28].…”
Section: Is Mho a "Benign" Phenotype?mentioning
confidence: 99%
“…In this sense, these phenotypes determinants and frequencies have not been deeply researched in Latin-American populations 7 . The objective of this study is to characterize, from a clinicalbiological point of view, the metabolic phenotypes in the population from Maracaibo city, Venezuela.…”
Section: Introductionmentioning
confidence: 99%